Opportunities for the development of hydrogen energy in the Murmansk region - A. A. Cheltybashev; Ia. M. Karachentseva (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. To analyze the perspectives for the development of hydrogen energy in the Murmansk region. To consider the possibility of implementing projects for producing "green" hydrogen for industrial using. METHODS. The method of analysis of literature sources in the field of hydrogen energy was used, as well as the method of generalizing the information obtained. RESULTS. The article describes the relevance of the topic, studies the global trend towards the transition to "green" energy. The methods of producing hydrogen are considered. The most environmentally friendly and efficient method for the production of industrial hydrogen has been identified, and possible sources of its production have been considered. CONCLUSION. As a result of the analysis of the prospects for the development of hydrogen energy in the Murmansk region, the prerequisites for the production of "green" hydrogen on an industrial scale are revealed. Possible sources for its production are listed. The article provides an example of the implementation of a project to create an international scientific research station on the territory of the Murmansk region, where hydrogen fuel cells will be used.